2009
DOI: 10.2337/dc08-1547
|View full text |Cite
|
Sign up to set email alerts
|

Is Femur Length the Key Height Component in Risk Prediction of Type 2 Diabetes Among Adults?

Abstract: OBJECTIVE -To examine the diabetes risk association with femur length, standing height, and height without femur length (HWFL) (HWFL ϭ standing height Ϫ femur length).RESEARCH DESIGN AND METHODS -We used data from three time periods of the National Health and Nutrition Examination Survey (1999 -2000, 2001-2002, and 2003-2004) for this cross-sectional analysis and confined the eligible subjects to 6,188 adults aged 20ϩ years who had fasted Ն8 h and had no missing values of femur length or standing height. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…In the meta‐analysis of HC and T2DM, we included five cross‐sectional studies (6–8,16,18) and six cohort studies (3–5,10,14,17). In the meta‐analysis of height and T2DM, we included four cross‐sectional studies (20–23) and five cohort studies (5,12–15).…”
Section: Resultsmentioning
confidence: 99%
“…In the meta‐analysis of HC and T2DM, we included five cross‐sectional studies (6–8,16,18) and six cohort studies (3–5,10,14,17). In the meta‐analysis of height and T2DM, we included four cross‐sectional studies (20–23) and five cohort studies (5,12–15).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of adult height and type 2 diabetes show heterogeneous results; one study showed inverse associations in both sexes, whereas other studies report significant inverse associations only among men or women or no significant association in either sex or in a men‐only or women‐only study . A large Israeli, men‐only study reported a HR of 0.88 for incident type 1 or type 2 diabetes per 5 cm greater height at age 30 years after adjustment for clinical and biochemical diabetes risk factors including BMI .…”
Section: Commentmentioning
confidence: 99%
“…Adult height is largely genetically determined, and it serves as a biological marker for many diseases with a positive association with cancer, and an inverse association with coronary heart disease and mortality . Associations between adult height and type 2 diabetes tend to show inverse associations, although there are inconsistencies across studies and by sex . Since adult height results from growth occurring in childhood, it is a period of life that warrants further investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the components of height are differentially associated with some cancers, 131 and leg length is linked to chronic heart disease 210 and diabetes. 211 Moreover, a recent study found little bias due to potential height loss in the estimates obtained from models using stature to predict health when controlling for age. 212 Potential confounding should not be ignored in the observed association between mothers' adult height and the health of their children.…”
mentioning
confidence: 99%